Expression of OCT4 isoforms is reduced in primary colorectal cancer - Turyova, Eva; Mikolajcik, Peter; Grendar, Marian; Kudelova, Eva; Holubekova, Veronika; Kalman, Michal; Marcinek, Juraj; Hrnciar, Matej; Kovac, Michal; Miklusica, Juraj; Laca, Ludovit; Lasabova, Zora (Frontiers in Oncology, 2023)
Introduction Colorectal cancer (CRC) is one of the most common types of cancer worldwide. The carcinogenesis of CRC is indeed complex, and there are many different mechanisms and pathways that contribute to the development of malignancy and the progression from primary to metastatic tumors. The OCT4A, encoded by the POU5F1 gene, is a transcription factor responsible for the phenotype of stem cells, maintaining pluripotency and regulation of differentiation. The POU5F1 gene is made up of five exons that can create numerous isoforms through alternative promoter or alternative splicing. In addition to OCT4A, other isoforms called OCT4B are also translated into protein; however, their role in cells has been unclear. The aim of our work was to investigate the expression patterns of OCT4 isoforms in primary and metastatic CRC, providing us with useful information about their role in the development and progression of CRC. Methods Surgical specimens from a total of 78 patients were collected and isolated from primary tumors (n = 47) and metastases (n = 31). The relative gene expression of OCT4 isoforms was investigated using the RT-qPCR method together with the TaqMan probes for particular OCT4 isoforms. Results Our results suggest significantly downregulated expression of the OCT4A and OCT4Bs isoforms in both primary (p = 0.0002 and p < 0.0001, respectively) and metastatic tumors (p = 0.0006 and p = 0.00051, respectively) when compared with the control samples. We also observed a correlation between reduced expression of all OCT4 isoforms and both primary and left-sided tumors (p = 0.001 and p = 0.030, respectively). On the other hand, the expression of all OCT4 isoforms was significantly upregulated in metastases compared with primary tumors (p < 0.0001). Discussion Unlike previous reports, we found out that the expression of OCT4A, OCT4Bs, and all OCT4 isoforms was significantly reduced in primary tumors and metastases compared with control samples. On the other hand, we supposed that the expression rate of all OCT4 isoforms may be related to the cancer type and side, as well as to liver metastases. However, further studies are required to investigate the detailed expression patterns and significance of individual OCT4 isoforms in carcinogenesis.